Prevalence of Obsessive-Compulsive Personality Disorder in Medical Students - Al-Na’she, Mohammad; Massad, Ahmad; Al Khraisat, Laith; Al Rafai, Mohammad; Albashtawi, Yahia; Almohtasib, Suliman; Alhayek, Ali; Elheet, Ahmad; Alaqtash, Ramzi; Jaber, Ruba (Jordan Medical Journal, 2024)
Objective: Obsessive-compulsive personality disorder (OCPD) is a cluster C personality disorder, and the most prevalent one. It is mainly characterized by perfectionism and can cause distress and functional impairment in the individual. This study aimed to determine the prevalence of OCPD in medical students, investigate the effect of this disorder on students’ academic performance, and discover any possible related factors. Methods: This cross-sectional observational study consisted of 508 medical students enrolled at the University of Jordan in 2021. It utilized a questionnaire that enquired about their sociodemographic information, academic information, and study habits. It also contained questions about the diagnostic criteria of OCPD from the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) and questions from the Personality Inventory for the DSM-5 (PID-5) to assess the presence of the rigid perfectionism personality trait. Results: Fifty-one percent of the studied sample either fulfilled the DSM-5 criteria or showed moderate or high expression of rigid perfectionism, according to the PID-5. More than two-thirds of the students able to be diagnosed with OCPD reported being overwhelmed with anxiety and stress at times of exams, and 41.5% stated that they skip sleep before exams even though they have finished studying. Conclusion: The reported prevalence of 51.18% in medical students is ten times the prevalence of OCPD in the general population. There was no association between OCPD and the students’ gender or academic performance. Students affected by OCPD seem to experience overwhelming amounts of stress and may need mental health support in the form of regular check-ups and counseling services.